Morality problems in ecology - R. M. Abakarova; O. S. Gadjimirzoeva (Юг России: экология, развитие, 2015)
Having been defined the position of morality in the modern ecological space it was found that ecological crisis increases because of spirit crisis, education crisis and human crisis. Defining the different levels of human spirituality it is revealed that at the highest level the nature is perceived as a human value, a value just as for people living in it.